1997
DOI: 10.1046/j.1365-2648.1997.1997026020.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric nurses' satisfaction: the effects of closure of a hospital

Abstract: A survey by questionnaire was carried out to examine the level of nursing staff satisfaction with the acute psychiatric services. Comparisons were made between views of older psychiatric hospitals and newer district general hospital units, and before and after the closure of Friern Barnet Hospital, London, England when the service was reorganized to include fewer beds. The importance of nurses having their say is emphasized, and areas in which improvements can be made are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…According to Levert et al (2000), burned-out workers show a lack of commitment and are less capable of providing adequate services, especially along dimensions of decision making and initiating involvement with clients (Maslach, 1982). According to Sammut (1997), burnedout workers are also too depleted to give of themselves in a creative, co-operative fashion.…”
mentioning
confidence: 99%
“…According to Levert et al (2000), burned-out workers show a lack of commitment and are less capable of providing adequate services, especially along dimensions of decision making and initiating involvement with clients (Maslach, 1982). According to Sammut (1997), burnedout workers are also too depleted to give of themselves in a creative, co-operative fashion.…”
mentioning
confidence: 99%
“…Burnt out employees show a lack of commitment and are less capable of providing sufficient services, mainly when it comes to aspects such as decision-making, thinking creatively and dealing with clients (Levert, Lucas & Ortlepp, 2000;Sammut, 1997;Fryer, Poland, Bross & Krugman, 1988). Employees suffering from high levels of burnout are characterised by cognitive impairment and report symptoms such as an inability to concentrate, forgetfulness, and difficulty with solving complex tasks (Hoogduin, Schaap, Methorst, Peters van Neyenhof & Van de Griendt, 2001).…”
Section: Burnout and Depressionmentioning
confidence: 99%
“…The extant literature related to inpatient psychiatric nurses was conducted in Australia and New Zealand (Berg & Hallberg, 2000;Cleary, 2004;Cleary & Edwards, 1999;Delaney, Clearly, Jordan, & Horsfall, 2001;Farrell & Dares, 1999;Fourie, McDonald, Connor, & Barlett, 2005;Happell, Martin, & Pinikahana, 2003;O'Brien & Cole, 2004;Taylor & Barling, 2004), Canada (Robinson, Clements, & Land, 2003), England (Callaghan, 1991;Fagin, Brown, Bartlett, Leary, & Carson, 1995;Fagin et al, 1996;Hall, 2004;Higgins, Hurst, & Wistow, 1999;Mistral, Hall, & McKee, 2002;Sammut, 1997;Sullivan, 1993;Whittington, 2002;Whittington & Wykes, 1992), Norway (Severinsson & Hummelvoll, 2001), Sweden (Severinsson & Hallberg, 1998), Japan (Ito, Eisen, Sederer, Yamada, & Tachimori, 2001), and a combination of two or more of the above countries (Melchior, Bours, Schmitz, & Wittich, 1997;Thomsen, Arnetz, Nolan, Soares, & Dallender, 1999).…”
Section: Nurse Practice Environmentmentioning
confidence: 99%
“…Moreover, psychiatric nurses identified that it was not only the number of staff members that was an issue, but it was also their level of competence and motivation (O'Brien & Cole, 2004;Sullivan, 1993). Other nurses reported that they did not feel safe in their work environment (Poster & Ryan, 1994;Sammut, 1997). Furthermore, the lack of other types of resources such as secretarial support increased nurses' administrative workload resulting in a decreased amount of time available for nurse-client interactions (Cleary, 2004;Cleary & Edwards, 1999;Fourie et al, 2005;Higgins et al, 1999).…”
Section: Nurse Practice Environmentmentioning
confidence: 99%
See 1 more Smart Citation